MSS-1 ～ MSS-2 (The Japanese Journal of SURGICAL METABOLISM and NUTRITION, 2017)
PURPOSE: Greater moderate-to-vigorous physical activity (MVPA) and light physical activity (LPA), with lower sedentary behavior (SED) during pregnancy are associated with more favorable maternal-child health. There is limited research examining the co-occurrence of these behaviors and who may be at risk for less optimal activity patterns across pregnancy. This study identifies and examines predictors of distinct activity profiles across pregnancy. METHODS: The present study is a secondary analysis of the Pregnancy 24/7 prospective cohort study (n=470). Participants wore a thigh-mounted accelerometer for up to 7 full days in each trimester to measure waking minutes per day of SED, LPA, and MVPA. Latent profile analysis identified distinct longitudinal activity patterns across pregnancy. Stepwise multinomial logistic regression examined predictors of profile membership. RESULTS: Five latent profiles were identified: High Sedentary (22%), Mixed Sedentary (34%), Mixed Active (25%), and High LPA (7%), High MVPA (12%). Activity patterns were stable across trimesters but differed substantially between profiles. Living with one or more children under age 5 (Relative risk ratio [RRR]: 2.15-3.84) and standing or active occupations (RRR: 9.25-45.77) were associated with greater likelihood of belonging to Mixed Active or High LPA profiles. Pre-pregnancy body mass index ≥30 kg/m² was associated with lower likelihood of membership in all more active profiles, particularly High MVPA (RRR: 0.13), compared to High Sedentary. Multiparous individuals were more likely to belong to higher LPA profiles, whereas nulliparous individuals were more likely to exhibit higher MVPA. CONCLUSIONS: Distinct patterns of activity occur across pregnancy. Those without children under age 5, in sedentary occupations, and with pre-pregnancy BMI ≥30 kg/m 2 had less favorable patterns and may benefit from targeted physical activity interventions to promote maternal-child health.